Filogeografia de um complexo deespécie crípticas de Bombus (Thoracobombus) brasiliensis lepeletier, 1836 - Jose Eustaquio dos Santos Junior (2011)
The genus Bombus (Latreille, 1802) has approximately 250 species commonly known as bumblebees. The genus has been recently reviewed and based on morphological, ecological, behavioral and genetic characters its subgeneric classification was reformulated, with the recognition of 15 subgenera. The Brazilian species, all formerly considered in the subgenus Fervidobombus, were included in Thoracobombus, together with species previously considered in the subgenera Eversmannibombus, Exilobombus, Laesobombus, Mucidobombus, Rhodobombus, Thoracobombus and Tricornibombus. Bombus brasiliensis is distributed in Brazil and in neighboring regions of Uruguay, Paraguay and Argentina. In Brazil, its distribution extends, in the east, along the coast, to southern Bahia state and, in the west, along the Paraná River basin (Mato Grosso do Sul and southern Goiás) and up to the southern portions of the Araguaia-Tocantins basin (Mato Grosso). To assess the distribution of the genetic variability of B. brasiliensis in a geographical and temporal context, a total of 144 specimens of B. brasiliensis were sequenced for the COI gene (471 bp) and 126 specimens for CytB gene (689 bp), both without deletions or insertions. In both genes ten haplotypes were detected and when concatenated (1157 bp) they comprised 26 haplotypes. According to the analysis, this taxon seems to consist of two species: B. brasiliensis itself, which is widely distributed, and another species (Bombus sp.n.), not described yet, with distribution restricted to the coast, from southern Bahia and northern Espírito Santo. Key